Application of Alpets (Animal Puppets) as A Media to Plant Anti Corruption Education to Students - Hanik Mufarida; Yunia Nur Rohmayani; Fajar Surya Hutama (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
Corruption is an act of abuse of power entrusted for personal gain, another person, or a group that can damage social governance and governance of state finances. The purpose of this study is to determine the effectiveness of anti-corruption learning through ALPETS (Animal Puppets) media. The method used in writing this scientific paper is descriptive qualitative. Data analysis techniques using content analysis. The application of ALPETS media is an effort to help students understand abstract concepts, such as corruption so as to minimize the occurrence of corruption through education. Innovation in the field of education in order to help the government minimize corruption crime through ALPETS (Animal Puppets) as a Media to Embed Anti-Corruption Education in Students.